The Evaluation of Equine Allogeneic Tenogenic Primed Mesenchymal Stem Cells in a Surgically Induced Superficial Digital Flexor Tendon Lesion Model - Depuydt, Eva; Broeckx, Sarah Y.; Van Hecke, Lore; Chiers, Koen; Van Brantegem, Leen; van Schie, Hans; Beerts, Charlotte; Spaas, Jan H.; Pille, Frederik; Martens, Ann (Frontiers in Veterinary Science, 2021)
Background: Tendon injuries are very common in horses and jeopardize the athletic performance, and due to the high risk of reinjury may lead to early retirement. The use of mesenchymal stem cells for the treatment of equine tendon disease is widely investigated because of their regenerative potential. The objective of this study is to investigate the safety and efficacy of equine allogeneic tenogenic primed mesenchymal stem cells (tpMSCs) for the management of tendinitis in horses. Methods: A core lesion was surgically induced in the superficial digital flexor tendon of both forelimbs of eight horses. After 7 days, one forelimb was treated with tpMSCs, while the contralateral forelimb served as an intra-individual control and was treated with saline. A prescribed exercise program was started. All horses underwent a daily clinical evaluation throughout the entire study period of 112 days. Blood samples were taken at different time points for hematological and biochemical analysis. Tendon assessment, lameness examination, ultrasound assessment and ultrasound tissue characterization (UTC) were performed at regular time intervals. At the end of the study period, the superficial digital flexor tendons were evaluated macroscopically and histologically. Results: No suspected or serious adverse events occurred during the entire study period. There was no difference in local effects including heat and pain to pressure between a single intralesional injection of allogeneic tpMSCs and a single intralesional injection with saline. A transient moderate local swelling was noted in the tpMSC treated limbs, which dissipated by day 11. Starting at a different time point depending on the parameter, a significant improvement was observed in the tpMSC treated limbs compared to the placebo for echogenicity score, fiber alignment score, anterior-posterior thickness of the tendon and echo type by UTC assessment. Immunohistochemistry 112 days post-injection revealed that the amount of collagen type I and Von Willebrand factor were significantly higher in the tendon tissue of the tpMSC group, while the amount of collagen type III and smooth muscle actin was significantly lower. Conclusion: Equine allogeneic tenogenic primed mesenchymal stem cells were shown to be well tolerated and may be effective for the management of tendon injuries.